DETERMINASI MOTIVASI KERJA UNIT PENGELOLA ZAKAT INFAK DAN SHODAQOH NAHDLATUL ULAMA TINGKAT KECAMATAN DI KABUPATEN MAGELANG - Ahmad Muhibin (Wahana Islamika Jurnal Studi Keislaman, 2022)
This study aims to determine the effect of organizational culture and organizational commitment on the work motivation of amil in UPZISNU Magelang Regency. The research data was collected using a questionnaire that was distributed to the UPZISNU administrators at the sub-district level in Magelang Regency. The research sample was 100 which was determined using the probability sampling method. Analysis of research data using multiple linear regression analysis techniques. The results of this study indicate that culture has no significant and negative effect on amil motivation in UPZISNU at the District level of Magelang Regency, this study rejects the supporting hypothesis. Organizational commitment has a positive and significant effect on the work motivation of amil in UPZISNU at the District Level in Magelang Regency, this study accepts the hypothesis that has been carried out so that job satisfaction has a positive and significant effect on work motivation for amil in UPZISNU at the District level of Magelang Regency.